Mortality and rehospitalization in patients with pre-existing implantable pacemakers undergoing catheter ablation are related to increased comorbidity burden: data from the German Ablation Registry - Frommeyer, Gerrit; Reinke, Florian Johann; Brachmann, Johannes; Lewalter, Thorsten; Tilz, Roland Richard; Willems, Stephan; Straube, Florian; Akın, Ibrahim; Lugenbiel, Patrick; Hochadel, Matthias; Senges, Jochen; Eckardt, Lars (Clinical research in cardiology, 2024)
Catheter ablation of atrial fibrillation and atrial flutter is routinely performed in patients with implantable devices. The aim of the present study was to assess success rates and potential complications in a large registry cohort of patients with cardiac pacemakers.